Pengaruh Pelatihan Terhadap Kualitas Tenun Di Kelompok Usaha Tenun Kada Situru' Desa Balla Kabupaten Mamasa - L, Eulogian Austro Pampang; Rasinan, Djusniati; Bandhaso, Mira La'bi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study examines the significant impact of training on the quality of woven products at the Kelompok Usaha Kada Situru’ in Desa Balla, Kabupaten Mamasa. The population in this study consists of members working at the Kelompok Usaha Tenun Kada Situru’ in Desa Balla, Kabupaten Mamasa. The sample size in this study is 44 respondents. Sampling was done by providing written statements or questions to respondents working at Kelompok Usaha Tenun Kada Situru’ in Desa Balla, Kabupaten Mamasa, to be answered. The data analysis methods used in this study include correlation coefficient analysis (r), coefficient of determination (r²), and the t-test. The results show that the training provided significantly influences the improvement of the quality of woven products, with a positive relationship between the intensity of training and the quality of the products produced by the business group members. These findings are expected to contribute to developing more effective training programs and policies to improve the quality of woven products and support the sustainability and competitiveness of woven products in the local market. Keywords:Training, Weaving Quality